MOF/Polymer-Integrated Multi-Hotspot Mid-Infrared Nanoantennas for Sensitive Detection of CO2 Gas - Zhou, Hong; Ren, Zhihao; Xu, Cheng; Xu, Liangge; Lee, Chengkuo (Nano-Micro Letters, 2022)
Metal–organic frameworks (MOFs) have been extensively used for gas sorption, storage and separation owing to ultrahigh porosity, exceptional thermal stability, and wide structural diversity. However, when it comes to ultra-low concentration gas detection, technical bottlenecks of MOFs appear due to the poor adsorption capacity at ppm-/ppb-level concentration and the limited sensitivity for signal transduction. Here, we present hybrid MOF-polymer physi-chemisorption mechanisms integrated with infrared (IR) nanoantennas for highly selective and ultrasensitive CO2 detection. To improve the adsorption capacity for trace amounts of gas molecules, MOFs are decorated with amino groups to introduce the chemisorption while maintaining the structural integrity for physisorption. Additionally, leveraging all major optimization methods, a multi-hotspot strategy is proposed to improve the sensitivity of nanoantennas by enhancing the near field and engineering the radiative and absorptive loss. As a benefit, we demonstrate the competitive advantages of our strategy against the state-of-the-art miniaturized IR CO2 sensors, including low detection limit, high sensitivity (0.18%/ppm), excellent reversibility (variation within 2%), and high selectivity (against C2H5OH, CH3OH, N2). This work provides valuable insights into the integration of advanced porous materials and nanophotonic devices, which can be further adopted in ultra-low concentration gas monitoring in industry and environmental applications. Highlights: 1 A loss-engineered multi-hotspot strategy is proposed by integrating all major optimization methods to improve the sensitivity and signal intensity of plasmonic nanoantennas for mid-infrared (MIR) absorption-based molecule sensing. 2 The physi-chemisorption mechanism of hybrid metal–organic framework (MOF)-polymers is demonstrated to break through the limit of detection for MIR gas sensing. 3 MOFs and nanoantennas are successfully integrated to achieve high-performance gas detection, including low detection limit, high sensitivity (0.18%/ppm), excellent reversibility (variation within 2%), high selectivity, and nm-level optical interaction length.